Preferences around the disclosure of dying: a vision from Portuguese society - Hilario, Ana Patricia (2019)
Objective This paper aims to explore the extent to which the “revivalist” discourse of a good death, which promotes an awareness of dying shapes the lived realities of palliative care patients and their families in Portugal. Method An ethnographic approach was developed. Participant observation was carried out in 2 palliative care units, and this was complemented by in-depth interviews. Ten terminally ill patients, 20 family members, and 20 palliative care professionals were interviewed. Results The “revivalist” good death script might not be suitable for all dying people, as they might not want an open awareness of dying and, thereby, the acknowledgment of imminent potential death. This might be related to cultural factors and personal circumstances. The “social embeddedness narrative” offers an alternative to the “revivalist” good death script. Significance of results The “revivalist” discourse, which calls for an open awareness of dying, is not a cultural preference in a palliative care context in Portugal, as it is not in accord with its familial nature.